Eksplorasi Etnomatematika pada Motif Batik Incung Kerinci - Junita Kumala Putri; Anisa Fitri; Nur Rusliah; Putri Yulia (ARITHMETIC: Academic Journal of Math, 2023)
Culture can be a place to learn mathematical concepts. One culture that contains elements of mathematics is the art of batik. The various batik motifs contain mathematical elements in them. One of the batiks that has various motifs is the Incung Kerinci Sungai Penuh batik. The aim of this study was to conduct an ethnomathematics study on the Incung Kerinci Sungai Penuh batik motif. The research method used in this study is a descriptive qualitative method with an ethnographic approach. Information was obtained through field observation techniques, interviews, and documentation. Researchers took pictures of batik cloth, then the results of the documentation were analyzed one by one to find mathematical concepts in each of the Incung Kerinci Sungai Penuh batik motifs. The subjects in this study were the owners of the Batik Incoang GNCE house located in the city of Sungai Penuh. The results showed that the Incung batik motif contained mathematical elements, in the form of flat geometric concepts such as rectangles, triangles, and circles. In addition to the concept of flat plane geometry, the Incung batik motif also contains mathematical concepts in transformation material, in the form of translations, reflections, and rotations.